2023
DOI: 10.3390/children10071250
|View full text |Cite
|
Sign up to set email alerts
|

Two Year Neurodevelopmental Outcome after Fetoscopic Laser Therapy for Twin–Twin Transfusion Syndrome: Comparison with Uncomplicated Monochorionic Diamniotic Twins

Abstract: Background: Twin–twin Transfusion Syndrome (TTTS) represents a significant complication in monochorionic twin pregnancies, caused by an unbalanced shunting of blood through intertwin placental vascular anastomoses. Despite advances in fetoscopic laser surgery, TTTS is still associated with a high rate of cerebral injury. However, there are no studies comparing these pregnancies with uncomplicated monochorionic diamniotic (MCDA) twin pregnancies, establishing the baseline risk of neurodevelopmental impairment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The results of our meta‐analysis showed no significant difference in the rate of PPROM among early TTTS cases undergoing FLS at <16 and 16–18 weeks’ GA. As the major challenge in TTTS, PTB is the most important risk factor for neonatal mortality and morbidity, particularly neurodevelopmental disabilities. 38 A recent study by Bartin et al. 23 showed that PTB at <28 weeks is significantly related to the GA at FLS and impacts neonatal morbidity among survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our meta‐analysis showed no significant difference in the rate of PPROM among early TTTS cases undergoing FLS at <16 and 16–18 weeks’ GA. As the major challenge in TTTS, PTB is the most important risk factor for neonatal mortality and morbidity, particularly neurodevelopmental disabilities. 38 A recent study by Bartin et al. 23 showed that PTB at <28 weeks is significantly related to the GA at FLS and impacts neonatal morbidity among survivors.…”
Section: Discussionmentioning
confidence: 99%